Cancer Patients' Use of the Internet to Search for Health Information: A Think-Aloud Study: Presenter(s): Fiorella Huijgens, Amsterdam University Medical Center, Netherlands. (April 2023) - Kwakman, Pascale; Smets, Ellen; Linn, Annemiek; van Weert, Julia; Hillen, Marij
Abstract : Background: The internet is one of the most frequently consulted sources for health information among cancer patients. Yet, it is not well understood how they obtain and assess health information while navigating the internet. We therefore aimed to explore the real-time online health information (OHI) seeking strategies of cancer patients in various stages of their disease trajectory. Methods: This study used a scenario-based online think-aloud approach. Participants (N = 15) were recruited from a panel of cancer patients, survivors and their caregivers. They were asked to seek OHI while imagining to be either a patient in the pre-diagnosis phase (N = 5), treatment phase (N = 5), or after their last treatment (N = 5). While searching, participants were encouraged to verbalize what they were thinking. Sessions were inductively coded and codes were categorized into overarching themes. Preliminary findings. Themes were: motives for going online, search approach, heuristics used to evaluate the information, coping strategies and emotions evoked. Motives for seeking OHI include reducing uncertainty and validating the treatment plan. Search approaches varied from exploratory to focused. Coping strategies included seeking multiple times a week and seeking distraction. When coming across cognitively or emotionally difficult information, participants either adapted their search strategy or stopped searching. Various heuristics were used. Emotions were present throughout the search process, ranging from anxiety to hope. Discussion: Our findings shed light on how cancer patients obtain and evaluate OHI. The results suggest that patients often use an exploratory search approach and can be guided by their emotions and heuristics while choosing information. Knowing how cancer patients search for and select OHI is the first step toward optimizing online health platforms, such that cancer patients can easily find and navigate through the information they seek.